1998
DOI: 10.1046/j.1365-2567.1998.00623.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization in vitro and in vivo of the pig analogue of human CD59 using new monoclonal antibodies

Abstract: CD59 is the sole characterized regulator of the complement membrane attack complex in humans. It is very widely and abundantly distributed, being present on all circulating cells, endothelia and epithelia, and in most tissues. CD59 analogues in rodents are distributed similarly. Interest in complement regulation in the pig has developed out of the current enthusiasm to exploit this species as a donor in xenotransplantation of organs to humans. We have recently isolated and cloned the pig analogue of human CD59… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 19 publications
1
22
1
Order By: Relevance
“…mCD59a was expressed, albeit weakly, in the white matter of the brain and cerebellum, whereas in humans, rats and pigs, white matter was CD59‐negative 22–24 . Purkinje cells in the mouse cerebellum were negative for mCD59a, as reported in the pig 24 . Expression of mCD59a in kidney was similar to that in human, rat and pig; glomeruli, distal tubules and collecting ducts all expressed high levels of mCD59a 22–24 .…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…mCD59a was expressed, albeit weakly, in the white matter of the brain and cerebellum, whereas in humans, rats and pigs, white matter was CD59‐negative 22–24 . Purkinje cells in the mouse cerebellum were negative for mCD59a, as reported in the pig 24 . Expression of mCD59a in kidney was similar to that in human, rat and pig; glomeruli, distal tubules and collecting ducts all expressed high levels of mCD59a 22–24 .…”
Section: Discussionmentioning
confidence: 64%
“…While, in most respects, the distribution of mCD59a was very similar to that of human CD59, there were interesting differences. mCD59a was expressed, albeit weakly, in the white matter of the brain and cerebellum, whereas in humans, rats and pigs, white matter was CD59‐negative 22–24 . Purkinje cells in the mouse cerebellum were negative for mCD59a, as reported in the pig 24 .…”
Section: Discussionmentioning
confidence: 79%
“…8±10, 15 However, it has since been demonstrated that CD59 will inhibit C from many other species, sometimes more ef®ciently than it regulates homologous C. 11,12,31 Several studies have used blocking antibodies to address the capacity of human DAF to regulate activation of C on the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…Complement deposition on the grafts was determined by staining with rabbit anti-human C3b (Biogenesis) and mouse anti-human C5b-9 (DAKO). Staining for CD59 was performed using mouse anti-swine CD59 (MEL) that was generously provided by Dr. B. Paul Morgan of the University of Cardiff, UK (17). …”
Section: Methodsmentioning
confidence: 99%